Performance of eggplant (Solanum melongena L.) antioxidant dietary fiber in a vegan cashew cream cheese - Higuera Coelho, Ricardo Alejandro (2025)
A vegan cashew cream cheese was developed with antioxidant dietary fibers extracted from discarded eggplants’ mesocarp + placenta + core (Mes) and peel + calyx (PC). The fibers were first characterized to evaluate their suitability as an additive/ingredient. PC fiber had higher pectin and cellulose contents, and lower lignin content than Mes fiber, explaining its greatest hydration capability. Both fibers showed high antioxidant activities, especially PC which showed higher contents of α-tocopherol, carotenoids, and extractable phenolics. While PC extractable phenolics had no antitumor effect on the HepG2 Hepatocellular Carcinoma Cell Line, Mes phenolics showed a 50 % cytotoxic concentration (CC50) of 133.2 ppm due to caffeoylquinic acid. Both fibers were added (5.0 %) to vegan cashew cream cheeses showing to be efficient antioxidant fibers delaying the peroxide index and TBARS increase during storage under refrigeration (8 °C). Simultaneously, the addition of PC fiber increased slightly both cheese dynamic moduli in the mechanical spectra, while the addition of Mes showed a slight decrease in moduli after 30 d. Eggplant dietary fibers can improve the nutritional profile and provide efficient, natural, healthy antioxidants for plant-based foods, especially those rich in unsaturated fatty acids like vegan cashew cream cheese.